Impact of a pharmacist‐physician collaborative care model on time‐in‐therapeutic blood pressure range in patients with hypertension. Issue 2 (1st May 2019) - Dixon, Dave L.; Parod, Eric D.; Sisson, Evan M.; Van Tassell, Benjamin W.; Nadpara, Pramit A.; Dow, Alan
Abstract: Introduction: Although pharmacist‐physician collaborative care models (PPCCM) improve mean blood pressure (BP) and goal attainment rates, the impact of these models on time‐in‐therapeutic blood pressure range (TTBPR) is unknown. Objectives: The primary objective of this study was to determine the effect of a PPCCM on TTBPR compared with a usual care group. Methods: This post‐hoc analysis compared data obtained from two retrospective groups of patients with uncontrolled hypertension managed either by a PPCCM or usual care. The primary end point was TTBPR, defined as the proportion of clinic visits with a systolic BP between 120 and 140 mmHg over a 12‐month follow‐up period. Several secondary end points were also evaluated. Means were compared using a t ‐test, while counts and comparisons were compared using chi‐square or Fisher exact test. Results: The study included 56 patients and 56 controls matched by gender, baseline systolic BP, and history of cardiovascular disease. Mean age was 58 years, 37.5% were female, and 73% were black. The mean TTBPR was 46.2% ± 24.3% in the PPCCM group and 24.8% ± 27.4% in the usual care group ( P < 0.0001). Therapeutic inertia was 20.1% in the PPCCM compared with 48.1% in the usual care group ( P < 0.0001). Greater reductions in BP were observed in the PPCCM group compared with usual care (systolic BP: −27.8 vs −11.4 mmHg, respectively; P < 0.0001; diastolic BP: −19.2 vs −4.2 mmHg, respectively; P < 0.0001). The BP control rates at 12 months were 89% in the PPCCM compared with 50% in the usual care group ( P < 0.0001). Conclusion: Patients exposed to a PPCCM had higher TTBPR compared with those who received usual care. The PPCCM group also had a lower rate of therapeutic inertia, greater reductions in BP, and achieved a higher percentage of patients at goal BP in an urban, underserved population.